Cartografía de la experiencia de un profesor y sus estudiantes en la Institución Educativa Villa de La Candelaria (2019)
In the context of the Master's program in Educational Sciences of the University of San Buenaventura, and within it, in the line of research in Contemporary Cultural Studies and Languages, it is carried out the research called Cartography of the experience of a teacher and his students in Villa de la Candelaria School. Its purpose was comprehensively study the experience, the different ways of being at school and the changes that arose once a change of name, in such institution, occurred. In this study, the cartographic method became important, since it allowed to build new ways of participation and to look inwards and outwards. The cartographic approach did not seek to analyze situations, not to mention, give solutions to alleged problems, rather it made it possible to go deeper in a process of construction of a view of school life, in which sensitivities were displayed, and thus they flow and mold the school’s everyday life